2007
DOI: 10.4037/ajcc2007.16.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Early Pneumoperitoneum After Percutaneous Endoscopic Gastrostomy in Intensive Care Patients: Sign of Possible Bowel Injury

Abstract: • Background Although percutaneous endoscopic gastrostomy may be complicated by iatrogenic bowel injury, most clinicians consider a small pneumoperitoneum on radiographs obtained after the procedure a benign finding of little clinical consequence. The possibility of a relationship between findings of early pneumoperitoneum after percutaneous endoscopic gastrostomy and subsequent iatrogenic bowel injury was examined. • Methods Charts of 85 patients in a surgical intensive care unit who had underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Another study also reported that a moderate or large pneumoperitoneum usually persists after 72 hours. 11 Given our results and previous reports, 2 12 13 14 complicated pneumoperitoneum cannot be predicted by the time to resolution and is unlikely to occur in patients with a small pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Another study also reported that a moderate or large pneumoperitoneum usually persists after 72 hours. 11 Given our results and previous reports, 2 12 13 14 complicated pneumoperitoneum cannot be predicted by the time to resolution and is unlikely to occur in patients with a small pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 53%
“…The incidence estimates for pneumoperitoneum in the literature range from 4.7%-55.6%. 8 13 Differences in methodology, expertise with the PEG technique, or endoscopic equipment explain some of the variability in the incidence. An imaging study after insertion of PEG is usually performed to assess complications such as pneumonia or fever.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some physicians have suggested that even without peritoneal signs and symptoms, iatrogenic bowel injury may be present and all pneumoperitoneum requires further diagnostic studies. 30 This is particularly true of ICU patients and those with altered mental status where the usual clinical symptoms of peritonitis can be masked. 31 If signs of peritonitis or infection are present, further evaluation is necessary.…”
Section: Mild Adverse Eventmentioning
confidence: 99%